Anti diabetic effect of ethanolic extract of leaves of Ocimum sanctum in alloxan induced diabetes in rats - S, Abhilash Rao; Y, Vijay; T, Deepthi; Ch, Sri Lakshmi; Rani, Vibha; Rani, Swetha; Y, Bhuvaneswara Reddy; P, Ram Swaroop; V, Sai Laxmi; K, Nikhil Chakravarthy; P, Arun (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes mellitus refers to a group of common metabolic disorders that share the phenotype of hyperglycemia resulting from defects of reduced insulin secretion, decreased glucose utilization and increase in glucose production. It is estimated that there are currently 285 million people worldwide and this number is set to increase to 438 million by the year 2030. India has the highest number of patients with known diabetes worldwide, with a prevalence of 11.6%. The aim of the study was to evaluate the anti diabetic activity of ethanolic extract of leaves of plant Ocimum sanctum in alloxan induced diabetes in rats. Methods: The study was conducted on 4 groups of 6 rats each to evaluate the hypoglycaemic effect of ethanolic extract of Ocimum sanctum. Glibenclamide was used as a standard drug and the results were compared in reference to it. Tween 80 was given for both normal and diabetic control groups. The fasting blood sugar levels were recorded on 1st, 3rd, 5th, 7th, 10th days by glucometer. Results: The results indicate that the test compound ethanolic extract of Ocimum sanctum has significant and sustained oral hypoglycaemic activity, comparable with the hypoglycaemic effect of glibenclamide, a sulfonylurea. Conclusion: The hypoglycaemic potential of the test compound is found to be comparable with that of the standard drug glibenclamide.